Enhancing Access to Learning through Blended Learning and Convergence Approaches in Open and Distance Education - Ojo, Olugbenga D. (West African Journal of Open and Flexible Learning, 2026)
The introduction of open and distance learning worldwide has resulted in a paradigm shift in the mode of education delivery. This shift has been accompanied by innovations in different elements of information and communications technologies. It also goes with approaches that are enhancing in the change of the old mode of education for real. This is facilitated by the creation and adoption of different strategies for promoting access to educational opportunities for all and sundry. This paper considers the role and impact of blended learning and the convergence of approaches on open and distance learning delivery modes of education in ODL institutions within West Africa. Blended learning and convergence approaches in ODL are discussed in relation to the viability of e-learning for improving the quality and reach of access to educational opportunities through the open and distance learning approach. The paper also concludes with some recommendations of sustainability strategies for implementing blended learning approaches in sub-Saharan Africa.